2021
DOI: 10.3390/su131911105
|View full text |Cite
|
Sign up to set email alerts
|

Housing Cost Burdens and Parental Support for Young Renters in South Korea

Abstract: In Korea, the housing issues faced by young renters negatively impact both their parents and themselves. This study aimed at exploring young renters’ situations whereby they receive financial support from their parents in order to pay current housing expenses, and their perception of housing cost burdens. Additionally, this study examined the influences on the reception of parental support and their perceived housing cost burdens. In February and March of 2021, an online questionnaire survey was conducted amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Depending on their parents' financial situation, young people's level of housing precarity and propensity to apply for a housing allowance programme varied. Since many young people must leave parental homes to move to metropolitan cities for education and employment (Jung, 2017; Kim & Yoo, 2021), the difference in parental financial assistance becomes a disparity in housing precarity (Hochstenbach & Boterman, 2017; Lee & Hwang, 2021). Young adults who receive at least a portion of their deposit and monthly rent from their parents can live in a relatively decent environment with a reasonable housing expense burden; those without parental support suffer the opposite circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on their parents' financial situation, young people's level of housing precarity and propensity to apply for a housing allowance programme varied. Since many young people must leave parental homes to move to metropolitan cities for education and employment (Jung, 2017; Kim & Yoo, 2021), the difference in parental financial assistance becomes a disparity in housing precarity (Hochstenbach & Boterman, 2017; Lee & Hwang, 2021). Young adults who receive at least a portion of their deposit and monthly rent from their parents can live in a relatively decent environment with a reasonable housing expense burden; those without parental support suffer the opposite circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Such financial dependence of co‐resident young adults also negatively impacts parents' well‐being (Aquilino, 1991). The housing expense burden is thus transferred to their parents, especially in Korea where parents strongly desire to support their children, thereby significantly straining retirement planning (Kwon & Jeon, 2020; Lee & Hwang, 2021). Using 2014 Korea Housing Survey microdata, Park and Lee (2015) found that nearly 30% of young renters living in either jeonse or paying monthly rent responded that their family provided financial support at an average of $29,727 per year.…”
Section: Literature Reviewmentioning
confidence: 99%